Synthesis, Characterization, and Application of Magnetic Mesoporous MCM-41-Fe3O4 Core-Shell Nanoparticles in the Removal of Eosin Yellow Dye - Alattar, Rawaa Abd; Mihsen, Hayder Hamied; Ahmed, Luma Majeed (Indonesian Journal of Chemistry, 2026)
Spinel ferrite (Fe3O4) nanoparticles have been produced as a black powder using precipitation and ultrasonic methods. The framework of MCM-41 was built using sodium silicate as the source of silica and CTAB as a template. Fe3O4 was immobilized on MCM-41 using the microwave method at 100 °C for 20 min, yielding MCM-41-Fe3O4 as a brown solid powder. This characterization was performed using FTIR, XRD, BET, TGA, FESEM-EDX, VSM, AFM, and TEM. The FTIR analysis demonstrated that the MCM-41-Fe3O4 had been properly synthesized. Two M−O bond peaks were discovered, one for the (Fe3+−O2−) octahedral site and one for the (Fe2+−O2−) tetrahedral sites. The XRD analyses revealed that MCM-41-Fe3O4 was synthesized with a highly ordered hexagonal building. The particles exhibited a spherical agglomeration and appeared smooth, as observed in TEM and FESEM examinations. The EDX analysis indicates that it was formed purely from Si, Fe, and O, with a weight percentage of 100%. BET analysis indicated that the sample had a relatively high surface area. In terms of a kinetic model, it was determined that a pseudo-second-order model provided the most suitable description. The thermodynamic study revealed that physical adsorption was exothermic and the adsorption process was nonspontaneous.